CRISPR screen reveals modifiers of rAAV production including known rAAV infection genes playing an unexpected role in vector production - Emily E. O’Driscoll; Sakshi Arora; Jonathan F. Lang; Beverly L. Davidson; Ophir Shalem (Molecular Therapy: Methods & Clinical Development)
Recombinant adeno-associated virus (rAAV) vectors are an effective and well-established tool in the growing gene therapy field, with five U.S. Food and Drug Administration-approved AAV-mediated gene therapies already on the market and numerous more in clinical trials. However, manufacturing rAAV vectors is an expensive, timely, and labor-intensive process that limits the commercial use of AAV-mediated gene therapies. To address this limitation, we screened producer cells for genes that could be targeted to increase rAAV yield. Specifically, we performed a CRISPR-based genome-wide knockout (KO) screen in human embryonic kidney (HEK) 293 cells using an antibody specific to intact AAV2 capsids coupled with flow cytometry to identify genes that modulate rAAV production. We discovered that the KO of a group of heparan sulfate biosynthesis genes previously implicated in rAAV infectivity decreased rAAV production. Additionally, we identified several vesicular trafficking proteins for which KO in HEK 293 cells increased rAAV yields. Our findings provide evidence that host proteins associated with viral infection may have also been co-opted for viral assembly and that the genetic makeup of viral producer cells can be manipulated to increase particle yield.